Analisis Nilai Karakter Islam dalam Matan Tuhfatu Al-Athfal dan Matan Al-Jazariyyah - Santosa, Aji Budi; Gumilar, Rizki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The degradation of ethics among Indonesia's younger generation has reached an alarming level, reflected in the prevalence of violence, sexual crimes, and the negative influence of social media. Failures in instilling noble values and the weak role of character education within curricula predominantly focused on cognitive aspects underscore the urgent need to revitalize the education system based on classical Islamic scholarship. Two monumental works, Tuḥfatul Aṭhfal and Al-Jazariyyah, frequently cited as primary references in Tajwid (Quranic recitation) studies, contain rich character values that remain underexplored. This study aims to identify the character values embedded within these two texts and evaluate their relevance to contemporary Islamic education. Employing a qualitative research methodology, it utilizes library research and content analysis of the primary texts (Tuḥfatul Aṭhfal and Al-Jazariyyah) along with secondary sources such as commentaries (syarah) and character education literature. The analysis revealed 12 core character values: God-consciousness, humility, respect for teachers, creativity, curiosity, discipline, social concern, patience, justice, continuous development, love of peace, and diligence. These values demonstrate strong relevance to the Ministry of Education and Culture's Character Education Strengthening Program (PPK) and offer solutions to the ongoing character crisis. Integrating these values into the formal curriculum through content integration, innovative teaching methods, and family-school collaboration is believed to be instrumental in shaping a generation possessing noble character and resilience in facing global challenges.